Multilayer bandpass filter using hairpin resonator for digital broadcasting: article / Ala Mohammed Saleh Alkubati - Alkubati, Ala Mohammed Saleh (2010)
This paper presents 12.2-12.75 GHz bandpass filter using multilayer hair-pin resonator for digital broadcasting applications. The multilayer coupled resonator RF filter shows a significant size reduction and increase the bandwidth have been designed with the five-pole resonator centered at 12.475 GHz with bandwidth of 550 MHz This filter is simulated on RO3003 substrate with dielectric 3 using Computer Simulation Technology software (CST) .